4,4′-Difluoro-[3,3′-bi(1,2,5-oxadiazole)] 2,2′-Dioxide - Natalia V. Obruchnikova; Oleg A. Rakitin (Molbank, 2023)
1,2,5-Oxadiazole oxides (furoxans) are well known nitric oxide donors; among them, 4-fluorofuroxans have recently been found to be important photoinduced nitric oxide donors. In this research, it was shown that the reaction of 4,4′-dinitro-[3,3′-bi(1,2,5-oxadiazole)] 2,2′-dioxide with fluoro-containing reagents (tetrabutylammonium fluoride or cesium fluoride) selectively gave the bis-substitution product 4,4′-difluoro-[3,3′-bi(1,2,5-oxadiazole)] 2,2′-dioxide. The structure of the synthesized compound was established by elemental analysis, 13C, 19F-NMR and IR spectroscopy, and mass-spectrometry.